2010
DOI: 10.1007/s11104-010-0315-4
|View full text |Cite
|
Sign up to set email alerts
|

Mentha spicata and Salvia fruticosa composts as soil amendments in tomato cultivation

Abstract: Τhe potential use of the aromatic plants Mentha spicata L. (spearmint) and Salvia fruticosa Mill. (sage) as soil amendments was evaluated. For this purpose, tomato seeds were sown in pots that had been filled with composts made from these plants and mixed with soil collected from an organically cultivated tomato field. A 2×2×4 [two types of fertilizer (synthetic and organic), two types of compost (M. spicata and S. fruticosa) and four compost rates (0%, 2%, 4% and 8%, w/w)] factorial experiment was used; the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 62 publications
0
19
0
Order By: Relevance
“…Yet this property does not bar them from persisting in the soil environment long enough to exert their effects. For example, in previous works by our team (Karamanoli et al 2008;Chalkos et al 2010), it was reported that spearmint essential oil persists long after addition to the soil, exhibiting a modified yet active composition.…”
Section: Discussionmentioning
confidence: 96%
“…Yet this property does not bar them from persisting in the soil environment long enough to exert their effects. For example, in previous works by our team (Karamanoli et al 2008;Chalkos et al 2010), it was reported that spearmint essential oil persists long after addition to the soil, exhibiting a modified yet active composition.…”
Section: Discussionmentioning
confidence: 96%
“…Different results were obtained in tests carried out by Chalkos et al (2010). These authors tested two species of Lamiaceae Family, Mentha spicata and Salvia fruticosa, using soil mixtures with both species, during 60 days.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, Argyropoulos et al [20] reported a negative effect on seed germination and seedling length for Mentha spicata essential oils not only in the case of weeds but also for tomato and cotton crops, while similar results have been reported for Mentha × piperita water extracts on tomato seeds germination and seedling growth. In contrast, Chalkos et al [23] reported that incorporating Mentha spicata composts in growth media at various rates (0-8% w/w) significantly increased tomato growth while inhibited weed emergence at the same time. In another study, Naeem et al [25] observed that rapeseed (Brassica napus L.) retarded the growth of maize seedlings, although the negative effects diminished at high salinity levels.…”
Section: Introductionmentioning
confidence: 93%
“…Peppermint (Mentha × piperita L.) and spearmint (Mentha spicata L.) are perennial aromatic plants cultivated worldwide [19], while both crops as well as other Mentha species exhibit allelopathic activity against weeds through their plant extracts or essential oils [20][21][22][23][24]. However, despite the positive effects of Mentha crops on weed control, their negative effects on plant growth and yield of crops has been observed.…”
Section: Introductionmentioning
confidence: 99%